Hubungan Kualitas Layanan Dan Harga Terhadap Kepuasan Pelanggan Warung Kopi Muhadi Di Kabupaten Jombang - Hermawan, Anugerah; Mahsuni, Abdul Wahid; Millaningtyas, Restu (E-JRM : Elektronik Jurnal Riset Manajemen, 2025)
Abstract This study aims to determine the relationship between service quality and price on customer satisfaction at Warung Kopi Muhadi in Jombang, particularly among students of Pondok Pesantren Darul ‘Ulum. The research method used is quantitative descriptive with purposive sampling of 130 respondents. Variables examined include service quality (reliability, responsiveness, assurance, empathy, tangibles), price (affordability, suitability, comparison, consistency), and customer satisfaction (repurchase intention and loyalty). Data were analyzed using Spearman rank correlation. The results show that both service quality and price have a significant and positive correlation with customer satisfaction.  Keywords: Service Quality, Price, Customer Satisfaction